Surpass Flow Diverter for Treatment of Posterior Circulation Aneurysms - Taschner, C.A.; Vedantham, S.; de Vries, J.; Biondi, A.; Boogaarts, J.; Sakai, N.; Lylyk, P.; Szikora, I.; Meckel, S.; Urbach, H.; Kan, P.; Siekmann, R.; et al. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Flow diverters for the treatment of posterior circulation aneurysms remain controversial. We aimed to identify factors contributing to outcome measures in patients treated with the Surpass flow diverter for aneurysms in this location.MATERIALS AND METHODS: We conducted an observational study of 53 patients who underwent flow-diverter treatment for posterior circulation aneurysms at 15 centers. Key outcome measures were mortality, complete aneurysm occlusion, and modified Rankin Scale score at follow-up.RESULTS: At follow-up (median, 11.3 months; interquartile range, 5.9–12.7 months), 9 patients had died, resulting in an all-cause mortality rate of 17.3% (95% CI, 7%–27.6%); 7 deaths (14%) were directly related to the procedure and none occurred in patients with a baseline mRS score of zero. After adjusting for covariates, a baseline mRS of 3–5 was more significantly (P = .003) associated with a higher hazard ratio for death than a baseline mRS of 0–2 (hazard ratio, 17.11; 95% CI, 2.69–109.02). After adjusting for follow-up duration, a 1-point increase in the baseline mRS was significantly (P < .001) associated with higher values of mRS at follow-up (odds ratio, 2.93; 95% CI, 1.79–4.79). Follow-up angiography in 44 patients (median, 11.3 months; interquartile range, 5.9–12.7 months) showed complete aneurysm occlusion in 29 (66%; 95% CI, 50.1%–79.5%).CONCLUSIONS: Clinical results of flow-diverter treatment of posterior circulation aneurysms depend very much on patient selection. In this study, poorer outcomes were related to the treatment of aneurysms in patients with higher baseline mRS scores. Angiographic results showed a high occlusion rate for this subset of complex aneurysms.BTbasilar trunkFDflow diverterHRhazard ratioKWANOVAKruskal-Wallis analysis of variancePCAposterior cerebral arteryQ1–Q3quartiles 1–3VBvertebrobasilar